Driving Lean Manufacturing through Corporate Governance and Intellectual Capital: The Moderating Influence of Organizational Culture - Saraswati, Rr Sri; Yadiati, Winwin; Suharman, Harry; Soemantri, Roebiandini (ADPEBI Publisher, 2025)
Purpose – This study examines the influence of corporate governance and intellectual capital on lean manufacturing implementation, with organizational culture as a moderating variable. Methodology/approach – A survey was conducted with 118 employees from manufacturing companies listed on the Indonesia Stock Exchange (IDX) with at least a Diploma (D3) degree and two years of experience. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings – Corporate governance and intellectual capital significantly enhance lean manufacturing practices. Organizational culture positively moderates these relationships, amplifying their effects. Novelty/value – This research integrates governance, intellectual capital, and culture as key determinants for lean success in Indonesian manufacturing firms, expanding the lean implementation literature in emerging markets.Keywords – Lean manufacturing, corporate governance, intellectual capital, organizational culture, PLS-SEM. Keywords: Corporate Governance, Intellectual Capital, Lean Manufacturing, Organizational Culture